Comparison of externally and internally guided dance movement to address mobility, cognition, and psychosocial function in people with Parkinson’s disease and freezing of gait: a case series - Abraham, Amit; Hart, Ariel; Bozzorg, Ariyana; Pothineni, Suraj; Wolf, Steven L.; Schuh, Kersey; Caughlan, Molly; Parker, Jelani; Blackwell, Amanda; Tharp Cianflona, Megan; Asker, Courtney; Prusin, Todd; et al. (Frontiers in Aging Neuroscience, 2024)
Objective: To explore the impact of internally guided (IG) versus externally guided (EG) adapted tango (AT) dance training (i.e., dancing the IG "Leader" role or the EG "Follower role), on motor and non-motor functions in individuals with Parkinson's disease and freezing of gait (PD-FOG).The "Leader" role, proxy for IG movements, conveys direction, timing and amplitude of steps with tactile cues. The "Follower" role, proxy for EG movements, detects and responds to the leader's tactile cues.Case Description: Six participants were randomly assigned to the IG ("Leader") or EG ("Follower") role for 20, ninety-minute long Adapted Tango (AT) lessons over 12 weeks.Participants were assessed for PD-specific and non-PD-specific functions before and twice after the end of the 12-week intervention, at 1 week and 1 month post intervention.: EG participants improved and/or maintained performance on more outcomes across all domains than IG participants. Five participants improved in PD motor symptoms, dynamic gait, global cognitive function and the FOG Questionnaire immediately or one month after intervention. All participants expressed positive attitudes toward the intervention, including improvements in walking, balance and endurance. Conclusion: Adapted Tango training in the Follower role may benefit individuals with PD-FOG to aa greater extent compared to the Leader role.